Temperature modelling within a thin material sheet involved in conductive‐radiative heat transfer - Birgelis, K. (Mathematical Modelling and Analysis, 2005)
In this paper we consider a problem about finding of temperature approximation within a thin material sheet involved in conductive‐radiative heat transfer. As result, we found that temperature within the sheet can be approximated in L 2 norm by solution of a simple nonlinear operator equation. Temperatūros modeliavimas tarp plonų medžiagos lakštų atsižvelgiant į radiacijai laidžios šilumos pernešimą Straipsnyje modeliuojamas temperatūros pasiskirstymas tarp plonų medžiagos lakštų atsižvelgiant į radiacijai laidžios šilumos pernešimą. Nustatyta, kad temperatūra tarp lakštų gali būti aproksimuojama L 2 normoje paprastos netiesinės operatorinės lygties sprendiniais. First Published Online: 14 Oct 2010